Seeing through the gray box: an integrated approach to physiological modeling of phytoplankton stoichiometry - Jones, Catriona L. C.; Camps-Castella, Judith; Smykala, Mike; Sobol, Morgan S.; Inomura, Keisuke (Frontiers in Ecology and Evolution, 2024)
The ‘black boxes’ of ecological stoichiometry, planktonic microbes, have long been recognized to have considerable effects on global biogeochemical cycles. Significant progress has been made in studying these effects and expanding our understanding of microbial stoichiometry. However, the ‘black box’ has not been completely cracked open; there remain gaps in our knowledge of the fate of elements within the phytoplankton cell, and the effect of external processes on nutrient fluxes through their metabolism and into macromolecules and biomass - the eponymous ‘gray box’. In this review paper, we describe the development of an integrative modeling approach that involves a stoichiometrically explicit model of Macromolecular Allocation and Genome-scale Metabolic Analysis (MAGMA) to gain insights into the intra- and extracellular fluxes of nutrients using the cyanobacterium Parasynechococcus marenigrum WH8102 as a target model organism. We then describe an example of the genome-scale resources for P. marenigrum that can be used to build such an integrated modeling tool to see through the gray box of phytoplankton stoichiometry and improve our understanding of the effects of resource supplies and other environmental drivers, especially temperature, on C:N:P demand, acquisition, and allocation at the cellular level.